Relationship of Explicitly and Implicitly Constrained Mixed Model - Dewi, Yuliani Setia (Majalah Ilmiah Matematika dan Statistika, 2017)
In linear models with independent observations, parameter constraints are usually handled by transforming the explicitly constrained model to implicitly constrained model, that takes the form of reduced-parameter. In this paper will be proofed that in mixed linear models (can used to analyze longitudinal data), explicitly constrained mixed model equivalent to the implicitly constrained mixed model with using general solution for linear equality constrains on the parameter.